Reviews (New blackfriars, 1967)
Reviews in this Article ST LUKE THEOLOGIAN OF REDEMPTIVE HISTORY, by Helmut Flender. SALVATION IN HISTORY, by Oscar Cullmann. THE GRAVE OF GOD. Has the Church a Future? by Robert Adolfs. AUGUSTINE OF HIPPO, by Peter Brown. CATHOLIC ACTION IN ITALY. The Sociology of a Sponsored Organization, by Gianfranco Poggi. WAR, CONSCIENCE AND DISSENT, by Gordon C. Zahn. THE MAKING OF A STATE EDUCATION SYSTEM. The passing of the New Zealand Education Act, 1877, by John Mackey. OBJECT RELATIONS, by David Holbrook. CHRISTIANITY AND THE ARTS, by Donald Whittle.